PRV-1b and PRV-3a infection is associated with the same clinical disease in coho salmon (Oncorhynchus kisutch) farmed in Chile: unraveling the pathogenesis of the orthoreoviral cardiomyopathy and hemolytic jaundice (OCHJ) - Marco Rozas-Serri; Ricardo Ildefonso; Andrea Peña; Victoria Jaramillo; Rodolfo Correa; Soraya Barrientos; Ariel Muñoz; Lucerina Maldonado; Estefanía Peñaloza (Veterinary Research)
Abstract Piscine orthoreovirus (PRV) is a virus that is widely distributed among global aquaculture populations of salmonid species. The coho salmon (Oncorhynchus kisutch) is a species of increasing productive and economic importance in Chile. The presence of PRV has generated concern about its impact on the health and welfare of this species. The objective of this study was to comparatively describe the clinical manifestations, pathological changes, and pathogenesis associated with PRV infection in two different farms of farmed coho salmon in Chile through a prospective longitudinal descriptive observational study. The results demonstrated that PRV-1b and PRV-3a are independently associated with the same clinical and pathological presentation in farmed coho salmon. Microscopic pathology of the disease associated with PRV-1b and PRV-3a was primarily characterized by degenerative and inflammatory findings in the heart and liver. Hematological and blood biochemistry biomarkers in fish exhibited alterations, manifesting as hemolytic anemia and prehepatic jaundice likely due to indirect hyperbilirubinemia. Pathogenesis of infection associated with both PRV-1b and PRV-3a would indicate a specific tropism for erythrocytes and cardiomyocytes of the spongy myocardium. It is noteworthy that despite a notable reduction in viral load of both PRV subgroups in tissues, the frequency of macroscopic lesions increased during the final phase of the study. In conclusion, the results indicate a strong correlation between infection by both PRV subgroups and the proposed orthoreoviral cardiomyopathy and hemolytic jaundice (OCHJ) disease. Further research on the pathogenesis and surveillance of PRV-1b and PRV-3a subgroups is pivotal to develop effective strategies for the control of OCHJ in farmed coho salmon.